1987
DOI: 10.3354/meps039001
|View full text |Cite
|
Sign up to set email alerts
|

Patchiness of epibenthic megafauna on the outer Grand Banks of Newfoundland

Abstract: ABSTRACT. Photographic transects were used to inveshgate the hstribution of megafauna in relation to substrate variability on the outer Grand Banks. Sedimentary cover consisted of reworked glacial deposits arranged in alternating bands of gravel and sand. Megafaunal density was higher along transects with elevational gradients of l m km-' than along transects with less gradient. Sessile, discretely motde, crawhng, and swimming animals were spahally autocorrelated as Indicated by significant increase in variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Firstly, the importance of these processes will be dependent on the spatial and temporal scales of observation or sampling (Dayton & Tegner 1984, Schneider et al 1987, Thrush et al 1997b). For example, Blanchard & Bourget (1999) related various aspects of physical heterogeneity of a rocky-shore coastline measured at multiple spatial scales to aspects of benthic community structure (including diversity) and showed that processes operating over different spatial scales best explained different aspects of community structure.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the importance of these processes will be dependent on the spatial and temporal scales of observation or sampling (Dayton & Tegner 1984, Schneider et al 1987, Thrush et al 1997b). For example, Blanchard & Bourget (1999) related various aspects of physical heterogeneity of a rocky-shore coastline measured at multiple spatial scales to aspects of benthic community structure (including diversity) and showed that processes operating over different spatial scales best explained different aspects of community structure.…”
Section: Introductionmentioning
confidence: 99%
“…data). There are many studies showing that higher density areas of the scallop species are in gravel and coarse sand sediment rather than in muddy or fine sand areas (Caddy 1970, Schneider et al 1987, Thouzeau et al 1991. Coarse grain sediment types have been generally associated with relatively strong current flow (Brand 1991) that provides favorable food conditions for the scallops.…”
Section: Distribution Patternsmentioning
confidence: 99%
“…Many factors affecting spatial distribution have been given, such as depth, substrate type (Caddy 1970, Schneider et al 1987, Thouzeau et al 1991, food availability, water currents (Olsen 1955, Thouzeau et al 1991, and predation (Langton & Robinson 1990). We detected contagious distribution patterns of the scallops within the fishing grounds on a large scale (in the order of a few km2) (Figs.…”
Section: Distribution Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early efforts used towed video and camera systems and manned submersibles to characterize and assess the spatial characteristics of seafloor communities along specified transects (e.g., Grassle et al 1975;Schneider et al 1987) and side-scan images to relate large-scale spatial changes in benthic community structure to environmental features such as tidal regime (Warwick and Uncles 1980) and disturbances (Menzie et. al.…”
mentioning
confidence: 99%